2011
DOI: 10.1371/journal.pone.0028455
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Approach to Study Floral Development Genes in Rosa sp.

Abstract: Cultivated for centuries, the varieties of rose have been selected based on a number of flower traits. Understanding the genetic and molecular basis that contributes to these traits will impact on future improvements for this economically important ornamental plant. In this study, we used scanning electron microscopy and sections of meristems and flowers to establish a precise morphological calendar from early rose flower development stages to senescing flowers. Global gene expression was investigated from flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 54 publications
2
29
0
1
Order By: Relevance
“…rosaceae.org/). Based on these data, expression profiles of 4,765 transcripts were detected in rose from floral transition to flower senescence using a newly developed Affymetrix microarray (Dubois et al, 2011). Moreover, application of next-generation sequencing technologies greatly promoted the study on rose genomics.…”
Section: Discussion Floral Transcriptome and Ethylene-responsive Profmentioning
confidence: 99%
See 1 more Smart Citation
“…rosaceae.org/). Based on these data, expression profiles of 4,765 transcripts were detected in rose from floral transition to flower senescence using a newly developed Affymetrix microarray (Dubois et al, 2011). Moreover, application of next-generation sequencing technologies greatly promoted the study on rose genomics.…”
Section: Discussion Floral Transcriptome and Ethylene-responsive Profmentioning
confidence: 99%
“…In addition, microarray analysis showed that expression of two AUX/IAA genes, one ARF gene, and one Brassinosteroid-regulated protein (Brassinosteroid Upregulated Protein1) gene were significantly altered during flower opening of Rosa spp. (Dubois et al, 2011). The integration of these hormonal signals into a model of petal growth requires further investigation.…”
Section: Discussion Floral Transcriptome and Ethylene-responsive Profmentioning
confidence: 99%
“…We identified over 100 transcripts likely involved in flower developmental processes (Additional file 10). These transcripts in Achimenes largely show similar expression patterns seen in other flowering plants [22, 25, 74]. The orthologs of many well-known MADS-box genes (e.g., AP1, AP3, PI, and AG ) are crucial for orchestrating floral organ identify [75, 76].…”
Section: Discussionmentioning
confidence: 89%
“…Linking protein evolution to the convergent evolution of these different pollination syndromes may provide evidence for shared or different genetic routes to these forms. Previous studies have suggested the pathways involved in pigment production, particularly anthocyanins, are involved in pollination syndrome transitions [45, 74, 75]. …”
Section: Discussionmentioning
confidence: 99%
“…However, these rose ESTs remained limited to genes expressed during floral development and to date sequence information for only about 5000 genes exists in the databases [4]. Despite their relatively limited number, the available ESTs for the rose have been valuable for the identification of several novel genes associated with flower characters such as the scent related germacrene D synthase, O-methyltransferases and alcohol acetyltransferase genes [3,5-10].…”
Section: Introductionmentioning
confidence: 99%